Comparative evaluation of post-operative pain after using manual irrigation and EDDY during root canal irrigation - Sara Paixão; Liliana Grenho; Cláudia Rodrigues (Sociedade Portuguesa de Estomatologia e Medicina Dentária, 2022)
Objectives: Post-endodontic pain (PEP) represents a significant challenge for dentists and patients. It can worsen patients' quality of life and teeth function. This study compared the risk of PEP between irrigations using an EDDY device and a conventional endodontic needle among patients seeking initial non-surgical root canal treatment. Methods: This prospective single-center randomized controlled clinical trial was conducted at the Dental Clinic of the Faculty of Dental Medicine of the University of Porto, Portugal. The participants were diagnosed with irreversible pulpitis or pulp necrosis. Eighty single-rooted teeth were randomly assigned to one of two irrigation groups: EDDY or manual syringe irrigation with needles with up-and-down movement (control group). PEP was assessed at 8, 24, and 48 hours postoperatively using the visual analog scale. Student's t-test, Kruskal-Wallis test, Pearson's chi-square test with Fisher's exact test, and Friedman's posthoc sign test were used. Results: Eight hours after irrigation, the EDDY group experienced a statistically significant higher incidence of pain (p=0.041) (52.5%) compared to the manual irrigation group (30%). There was no statistically significant difference between groups regarding the PEP 24 hours (p=0.068) and 48 hours (p=0.433) after RCT. Conclusions: EDDY irrigation during initial RCT is associated with a higher incidence of PEP, mainly in the first 24 hours, compared to manual irrigation. Afterward, the rate of PEP was similar between groups, with a gradual decline in pain intensity